Entrepreneurship in higher education: The role of incentives and the impact of academies on the motivations to undertake and entrepreneurial potential of students - Eghteda, Samuel Nejati (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação